PENERAPAN ELIMINATION AND CHOICE TRANSLATION REALITY (ELECTRE) DALAM PENENTUAN KULKAS TERBAIK - Saputra, Imam; Sari, Sri Indah; Mesran, Mesran (STMIK Budi Darma, 2017)
Electronic products is one of the household needs tools needed by the community because it has a small size and the price is not too expensive compared to other equipment needs. Currently many types and brands of electronic product variants with advantages and advantages. One of the products needed by the community is the Refrigerator. So many types and brands of refrigerators circulating in the market today. Of course this greatly affects consumers in determining the appropriate choice with the refrigerator required. To overcome this, it is necessary a decision support that can assist consumers in determining the choice. Some methods can be used in decision support such as AHP, TOPSIS, SAW, WP, ELECTRE, but in this study researchers chose ELECTRE.